Харків: номен і образ в українській поезії - Тєлєжкіна, О. (Культура слова, 2021)
У статті власну назву Харків розглянуто як онім, що виконує певне прагматичне навантаження, і як образно-метафоричний компонент поетичного тексту. Автор доходить висновку, що досліджувана назва є носієм глибинного значення, увиразнення якого уможливлює розкриття її стилістичних потенцій: онім утворює близькозвучні сполуки, опозиційні пари, метонімічні одиниці, виступає актуалізатором відповідних міжтекстових зв’язків і маркером певних історичних, соціально значущих культурних чи політичних подій. У проаналізованих поетичних творах онім Харків є органічним структурним складником, який стає виразником задуму митця. In the articleit has been discovered the notable manifestations the name Kharkiv on the material of Ukrainian poetry of the twentieth century. The expediency of such an analysis confirms the fact that the named onym has been overlooked in scientific research on literary onomastics. The author concludes that the proper name Kharkiv in the works of Ukrainian poetry is represented not only as a purely onomastic unit that performs certain pragmatic functions (nominative, localization) but also as a carrier of deep meaning, the expression of which allows the disclosure of its figurative and metaphorical potentials: compounds and oppositional pairs which allows a sharper characterization of the phenomenon described in the poetic work; metonymic units, serves as an indicator of relevant intertextual connections and a marker of certain historical, significant cultural or political events, establishing the semantic relationship between the poetic text and the background knowledge of the reader. It has been found out that Kharkiv is an organic structural component that actualizes certain information and becomes a significant expression of the author’s semantic intentions in analyzed poetic works.